2016
DOI: 10.3389/fendo.2016.00144
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Cytosolic DNA Fragments as a Potential Trigger of Graves’ Disease: An Encrypted Message Sent by Animal Models

Abstract: Graves’ hyperthyroidism is caused by autoantibodies directed against the thyroid-stimulating hormone receptor (TSHR) that mimic the action of TSH. The establishment of Graves’ hyperthyroidism in experimental animals has proven to be an important approach to dissect the mechanisms of self-tolerance breakdown that lead to the production of thyroid-stimulating TSHR autoantibodies (TSAbs). “Shimojo’s model” was the first successful Graves’ animal model, wherein immunization with fibroblasts cells expressing TSHR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 74 publications
0
9
0
3
Order By: Relevance
“…Memory B cells are formed within germinal centers and differ from naive B cells with respect to several features. While many human and murine memory B cells still express IgM, a significant proportion has already switched to the production of downstream antibody subclasses, mainly IgA and IgGs ( 29 31 ). Antigen-mediated crosslinking of membrane IgG provides a much stronger activation signal than IgM ( 32 ), which contributes to the reduced activation threshold observed for memory B cells and their capacity to quickly give rise to antibody-secreting plasma cells ( 33 36 ).…”
Section: B Cells Plasma Cells and Their Impact On Autoimmune Diseasmentioning
confidence: 99%
“…Memory B cells are formed within germinal centers and differ from naive B cells with respect to several features. While many human and murine memory B cells still express IgM, a significant proportion has already switched to the production of downstream antibody subclasses, mainly IgA and IgGs ( 29 31 ). Antigen-mediated crosslinking of membrane IgG provides a much stronger activation signal than IgM ( 32 ), which contributes to the reduced activation threshold observed for memory B cells and their capacity to quickly give rise to antibody-secreting plasma cells ( 33 36 ).…”
Section: B Cells Plasma Cells and Their Impact On Autoimmune Diseasmentioning
confidence: 99%
“…Many studies have demonstrated that the main hormones involved in the regulation of thyroid growth and function decrease MHC class I expression, which include thyroid-stimulating hormone (TSH), insulin/ insulin-like growth factor (IGF)-I and hydrocortisone, ( 17 , 29 31 ). MHC class I overexpression, as well as MHC class II aberrant expression, on non-immune cells is a feature of autoimmune diseases and thyroid autoimmunity ( 27 , 32 37 ). The hormonal regulation of MHC molecules in thyroid cells is considered important for the suppression of autoimmunity during hormonally induced changes in cellular growth and function, which results in enhanced expression of potential thyroid autoantigens, such as thyroglobulin, thyroid peroxidase, and the TSH receptor (TSHR).…”
Section: Nf-κb and The Thyroidmentioning
confidence: 99%
“…При воздействии лиганда (ТТГ, ТСА) происходит диссоциация G-белка с образованием 2 субъединиц -Gα и Gβγ. Передача сигнала внутрь тиреоцита осуществляется в основном за счет субъединицы Gα, а также через вторичную аденилатциклазную сигнальную систему (путь протеинкиназы типа А), в меньшей степени задействуется вторичный сигнальный путь протеинкиназы типа С (для активизации последней требуется больший уровень ТТГ) [15,16,[40][41][42][43].…”
Section: злокачественное новообразование и бгunclassified
“…В последнее время в связи с рутинным применением генетических исследований и накоплением новых данных, полученных на животных моделях, исследователи вновь заговорили о первичных изменениях в самой ЩЖ как о пусковом механизме БГ [43,51]. В 3 недавних метаанализах определен однонуклеотидный полиморфизм гена TSHR (точечные мутации гена в интроне 1 -rs179247, rs12101255), который имеет сильную корреляцию с БГ [51].…”
Section: злокачественное новообразование и бгunclassified
See 1 more Smart Citation